Selective weed and ground cover management in a coffee plantation with shade trees in Nicaragua - Aguilar Bustamante, V.M. (Uppsala (Suecia), 2001)
Sumario (En)
Ilus.
Tesis (Dr)
Keywords: COFFEA ARABICA; MALEZAS; MANEJO DEL CULTIVO; AGROFORESTERIA; RESIDUOS; BIOMASA; NICARAGUA